Zoonoses and traumatic injuries among practicing veterinarians from Southern Chile - Herrera-Rosales, Luciano; Azócar-Aedo, Lucía; Cabello-Stom, Javier (Austral Journal of Veterinary Sciences, 2023)
This research addresses the occurrence of clinical signs and related symptoms of zoonotic diseases, traumatic injuries, and the frequency of healthcare seeking among practicing veterinarians, whose job was performed in the Los Lagos Region, Southern Chile. An online standardized survey collected from 140 practicing veterinarians was conducted between March and July 2020. The surveyed participants reported the occurrence of brucellosis, ringworm, scabies, cat scratch disease, anthrax, toxocariasis, salmonellosis, pediculosis, and flea infestation among veterinarians. The clinical signs and symptoms related to these events include diarrhea, allergies, and muscle pain. Mild and severe traumatic injuries were also declared by the participants, in which the frequency of severe trauma increased as the time of professional practice increased. Nevertheless, the use of professional healthcare was low among the surveyed veterinarians. This study emphasizes the need to consider veterinarians’ health-related occupational risks using the “One Health” approach.